Fundamental Financial Performance Analysis And Stock Valuation Of PT DCI Indonesia TBK At Year 2024 - Hermawan, Mega; Noveria, Ana (Jurnal Locus Penelitian dan Pengabdian, 2025)
Indonesia’s rapid digital transformation has significantly increased demand for data center services, positioning PT DCI Indonesia Tbk (DCII) as a key player. Since its IPO in 2021, DCII’s share price has grown sharply, reaching IDR 42,100 by the end of 2024. However, this steep valuation prompts an important question: does the market price reflect the company’s financial fundamentals, or is it driven by speculative sentiment? This research aims to evaluate the intrinsic value of DCII and assess whether its stock is overvalued. The study adopts a multi-method approach. First, a financial performance analysis was conducted using key ratios from 2021 to 2024, including liquidity, profitability, solvency, and efficiency metrics. The results indicate strong profitability and revenue growth, but also reveal financial pressure in the form of weakening liquidity ratios and increasing collection periods. Second, the study applies a multi-stage Discounted Cash Flow (DCF) model to estimate DCII’s intrinsic equity value. Free cash flow is projected over a 15-year horizon to reflect the company’s life cycle, with a terminal value based on a 4% growth rate and a WACC of 12.85%. The resulting fair value is IDR 18,529 per share—less than half of the market price. To strengthen the valuation, a Comparable Company Analysis (CCA) was also conducted, comparing DCII with similar firms in the digital infrastructure sector. The findings show that DCII trades at a substantial premium across valuation multiples, including EV/EBITDA and P/E. Sensitivity analysis further confirms that, even under optimistic assumptions, DCII’s intrinsic value remains significantly below its current market price. The evidence suggests that investor expectations have outpaced financial fundamentals, presenting risks to long-term shareholder value. Based on these findings, the thesis proposes three recommendations: (1) executing a 1:3 stock split with insider lock-up to enhance liquidity and signal long-term commitment; (2) issuing a quarterly business bulletin to guide investor expectations through strategic and financial updates; and (3) implementing a focused working capital optimization program to address emerging liquidity risks. These initiatives aim to reduce valuation misalignment and support sustainable growth. Future research may extend this analysis across Southeast Asian firms and incorporate qualitative factors such as ESG and customer concentration into valuation models.